2021
DOI: 10.1177/21677026211017835
|View full text |Cite
|
Sign up to set email alerts
|

High Predictive Accuracy of Negative Schizotypy With Acoustic Measures

Abstract: Negative schizotypal traits potentially can be digitally phenotyped using objective vocal analysis. Prior attempts have shown mixed success in this regard, potentially because acoustic analysis has relied on small, constrained feature sets. We employed machine learning to (a) optimize and cross-validate predictive models of self-reported negative schizotypy using a large acoustic feature set, (b) evaluate model performance as a function of sex and speaking task, (c) understand potential mechanisms underlying n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Also, within the context of subclinical psychosis, studies using schizotypy as a framework have provided valuable insights [to the deeper understanding of schizotypy concept, the authors suggest reading the work of (61)(62)(63)]. High level of schizotypy has been associated with alterations in speech production, speech variability, and speech content (64)(65)(66). Furthermore, studies have demonstrated that individuals with high schizotypy exhibit alterations in acoustic features of speech like reduced speech variability, expressiveness and atypical pitch patterns compared to those with lower schizotypy scores (20,67).…”
Section: Speech Techniques and Analysis Applied In Subclinical Popula...mentioning
confidence: 99%
“…Also, within the context of subclinical psychosis, studies using schizotypy as a framework have provided valuable insights [to the deeper understanding of schizotypy concept, the authors suggest reading the work of (61)(62)(63)]. High level of schizotypy has been associated with alterations in speech production, speech variability, and speech content (64)(65)(66). Furthermore, studies have demonstrated that individuals with high schizotypy exhibit alterations in acoustic features of speech like reduced speech variability, expressiveness and atypical pitch patterns compared to those with lower schizotypy scores (20,67).…”
Section: Speech Techniques and Analysis Applied In Subclinical Popula...mentioning
confidence: 99%
“…In mental health research, speech changes are analysed in terms of language use and vocal parameters, usually after sampling a few minutes of speech elicited with standardized prompts and applying computerized, automated techniques to extract different features of speech. Vocal or paralinguistic analysis evaluates the physical aspects of spoken language after representing sound as waveforms and extract temporal, prosodic or frequency features regarding formants, pitch, frequency, duration, pauses and volume (Agurto et al, Jul 2020b;Albuquerque et al, 2021;Coelho et al, 2021;Cohen et al, 2022;Olah et al, 2023). The modern analysis of language use leverages Natural Language Processing, applied on speech transcripts.…”
Section: Introductionmentioning
confidence: 99%